The state and prospects of tourism industry in the conditions of the digital economy (Journal of Economic Research & Business Administration, 2018)
Tourism is one of the most successful and dynamically developing sectors of the world economy.This is evidenced by the share of tourism (about 10%) in world GDP. Being the most successful businessin the world, tourism is the most important source of the state budget.The article examines the current state of tourism in the digital economy and its contribution to theeconomy. Particular attention is paid to changes and innovations in the field of digital economy. Thepurpose of the article is to reveal the advantages of the development of digital tourism and the prospectsfor its development. New opportunities in tourism in the digital economy are analyzed. In the developmentof digital tourism, this is directly related to the fact that today’s world community can’t be imaginedwithout any portable technical devices. The development of tourism in the digital economy will help to strengthen competition betweenstates, improve people’s well-being and provide jobs. Tourism also solves social problems associatedwith preserving traditional opportunities and balancing international partnerships between states.